C’est la cité ! - Philippe Woloszyn; Paul Girard (Projets de Paysage)
This study seeks to understand the ways in which elements of urban landscapes filmed in a rap video clip are perceived by reinterpreting the context which provides the background to the positions of local stakeholders. This implementation of an activist stance is analysed from the perspective of the spatial language adopted by the camera within the landscape of the Clairière des Aubiers, a large Bordeaux housing project where the video clip was filmed. The study of the discourse developed in this audiovisual document aims to bring out the linguistic and metalinguistic patterns defining the socio-cultural framework of the Clairière des Aubiers, while the study of the images is intended to provide keys for interpreting the singular iconic relationship between rappers and the landscape in their daily lives. In doing so, we study the capacity of a medium such as this video clip to reveal all or part of the social reality of a residential area through its portrayal of an ambience and, by the same way, the role of the landscape in the construction of the revealed living environmental identity.